2023
DOI: 10.3892/ol.2023.13740
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment levels of serum alkaline phosphatase are associated with the prognosis of patients with non‑small cell lung cancer receiving immune checkpoint inhibitors

Abstract: Immune checkpoint inhibitors (ICIs) have been an encouraging treatment method in non-small cell lung cancer (NSCLC). However, bone and liver metastases are considered to restrain immunotherapy efficacy. Since serum alkaline phosphatase (ALP) is associated with bone and liver metastases, it was investigated whether serum ALP could be a novel biomarker to predict the efficacy of ICIs treatment. In the present study, 143 patients with NSCLC receiving ICIs treatment were retrospectively analyzed. The objective res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…While research on ALP has demonstrated their potential as biomarkers across different tumour types, its role in NSCLC remains uncertain (Jiang et al 2023 ), and literature concerning NSCLC patients receiving immunotherapy is limited. Yang et al ( 2023 ) found that higher levels of pre-treatment ALP are associated with lower overall response rate, and shorter median progression-free survival (mPFS) in patients with NSCLC treated with immune checkpoint inhibitors and that ALP is an independent prognostic indicator of mPFS. Julian et al ( 2022 ) found that high levels of ALP were a risk increasing prognostic factor in advanced NSCLC patients receiving anti-PD-1/PD-L1 immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…While research on ALP has demonstrated their potential as biomarkers across different tumour types, its role in NSCLC remains uncertain (Jiang et al 2023 ), and literature concerning NSCLC patients receiving immunotherapy is limited. Yang et al ( 2023 ) found that higher levels of pre-treatment ALP are associated with lower overall response rate, and shorter median progression-free survival (mPFS) in patients with NSCLC treated with immune checkpoint inhibitors and that ALP is an independent prognostic indicator of mPFS. Julian et al ( 2022 ) found that high levels of ALP were a risk increasing prognostic factor in advanced NSCLC patients receiving anti-PD-1/PD-L1 immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is worth noting that a deficiency in ALP can also have negative implications for cancer patients. Studies have shown that low levels of ALPs are linked to poorer outcomes in individuals with specific types of tumors, such as CRC, breast cancer, and NSCLC ( 44 , 47 - 52 , 54 , 55 ). This is because reduced ALP activity may be indicative of decreased differentiation among cancer cells, meaning they are less specialized and more likely to grow uncontrollably.…”
Section: Discussionmentioning
confidence: 99%
“…ALP has also been studied as a potential biomarker in NSCLC patients, though the results of studies have been inconsistent ( 38 ). Some studies have reported that high levels of ALP are associated with a poorer prognosis and shorter survival time in NSCLC patients, while others have found no significant correlation between ALP levels and prognosis in NSCLC ( 38 , 54 , 55 ). In addition to being a potential marker of bone metastases, ALP may also be involved in promoting tumor growth and invasion in NSCLC.…”
Section: Alps In Non-small Cell Lung Cancer (Nsclc)mentioning
confidence: 99%